2019
DOI: 10.1155/2019/4529830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chilled Ageing Conditioning at 4°C in Lamb Longissimus Dorsi Muscles on Water-Soluble Flavour Precursors as Revealed by a Metabolomic Approach

Abstract: The objective of this study was to investigate, by a metabolomic approach, the effects of chilled ageing conditioning at 4°C in lamb longissimus dorsi (LD) muscles on water-soluble flavour precursors. The results showed that the content of nucleotide degradation products significantly increased (P<0.05) due to the adjusted biosynthesis of alkaloids derived from histidine and purine from day 0 to day 4. Additionally, the content of glycolytic compounds significantly increased (P<0.05) due to enhanced glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Many studies showed that apoptosis improves the tenderness of meat effectively (Huang et al ., 2009; Wang et al ., 2018). Previously, we found that the accumulation of IMP and amino acids occurred in the later stage of ageing rather than in the early stage (You & Luo, 2019). This could be due to apoptosis associated with an IMP increase (Ferrari et al ., 1998).…”
Section: Discussionmentioning
confidence: 85%
“…Many studies showed that apoptosis improves the tenderness of meat effectively (Huang et al ., 2009; Wang et al ., 2018). Previously, we found that the accumulation of IMP and amino acids occurred in the later stage of ageing rather than in the early stage (You & Luo, 2019). This could be due to apoptosis associated with an IMP increase (Ferrari et al ., 1998).…”
Section: Discussionmentioning
confidence: 85%
“…The sample derivation was completed following the experimental protocols of You and Luo ( 2019 ). Each sample (30 mg) was transferred to a 1.5‐mL Eppendorf tube, treated with 2‐chloro‐l‐phenylalanine (20 μ l, 0.3 mg/ml, Hengbai Biotechnology Co., Ltd., Shanghai, China) in methanol (CNW Technologies GmbH, Düsseldorf, Germany), and ground (60 HZ, 120 s) after being stored at −80 ºC for 2 min, and added with 120 μ l of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the present study, Koutsidis, Elmore, Oruna-Concha, Campo, Wood and Mottram [21] reported that free amino acids like threonine, phenylalanine, isoleucine contributed to brown/roasted flavour of beef, which were desirable to consumers. Moreover, free amino acids like tyrosine, phenylalanine, and threonine contributed to the tenderisation and flavour enhancement in lamb longissimus dorsi muscles treated with chilled ageing conditioning at 4 • C on the 8th day of storage [26].…”
Section: Chilled Samplesmentioning
confidence: 98%